Encapsulation and Melanization Are Not Correlated to Successful Immune Defense Against Parasitoid Wasps in Drosophila melanogaster - Lilla B. Magyar; István Andó; Gyöngyi Cinege (Cells)
Parasitoid elimination in Drosophila melanogaster involves special hemocytes, called lamellocytes, which encapsulate the eggs or larvae of the parasitoid wasps. The capsules are melanized, and metabolites of the melanization reaction may play a potential role in parasitoid killing. We have observed a variation in the melanization capacity of different, commonly used D. melanogaster strains, such as Canton-S, Oregon-R, and BL5905, BL6326. In this work, we aimed to clarify a possible connection between the effectiveness of capsule melanization and the success of parasitoid elimination following infection with Leptopilina parasitoid wasps. Circulating hemocytes and lamellocyte attachment were visualized by confocal and epifluorescence microscopy using indirect immunofluorescence. Expression profiles of the PPO2 and PPO3 prophenoloxidase genes, which encode key enzymes in the melanization reaction, were detected by qRT-PCR. Parasitization assays were used to analyze fly and wasp eclosion success. Active encapsulation and melanization reactions against Leptopilina boulardi were observed in the BL5905 and the BL6326 strains, though restricted to the dead supernumerary parasitoids, while fly and wasp eclosion rates were essentially the same in the four examined D. melanogaster strains. We conclude that encapsulation and melanization carried out by D. melanogaster following L. boulardi infection have no impact on survival.